Role of NO and S-nitrosylation in the Expression of Endothelial Adhesion Proteins That Regulate Leukocyte and Tumor Cell Adhesion - Aguilar, Gaynor; Koning, Tania; Ehrenfeld, Pamela; Sánchez, Fabiola A. (Frontiers in Physiology, 2020)
Leukocyte recruitment is one of the most important cellular responses to tissue damage. Leukocyte extravasation is exquisitely regulated by mechanisms of selective leukocyte-endothelium recognition through adhesion proteins in the endothelial cell surface that recognize specific integrins in the activated leukocytes. A similar mechanism is used by tumor cells during metastasis to extravasate and form a secondary tumor. Nitric oxide (NO) has been classically described as an anti-inflammatory molecule that inhibits leukocyte adhesion. However, the evidence available shows also a positive role of NO in leukocyte adhesion. These apparent discrepancies might be explained by the different NO concentrations reached during the inflammatory response, which are highly modulated by the expression of different nitric oxide synthases, along the inflammatory response and by changes in their subcellular locations.